Illyrian pre-Alpine fir and beech forests – the association Homogyno sylvestris-Fagetum Marinček et al. 1993 - Marinček, Lojze; Čarni, Andraž (Hacquetia, 2015)
The work deals with the association Homogyno sylvestris-Fagetum in the pre-Alpine region of Slovenia. The communitis were classified into a geographical race typica and divided into six subassociations: typicum subass. nova, mercurialetosum perennis subass. nova, festucetosum altissimae subass. nova, calamagrostietosum variae subass. nova, luzuletosum sylvaticae subass. nova and vaccinietosum myrtilli subass. nova. The results are shown in the analytical table, as well as in two diagrams.